Peran Iklan Storytelling dalam Meningkatkan Engagement Produk Eatsambel pada Aplikasi Tiktok - Maulida, Shanaya Layla; Isnaini, Wiwi (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
Eatsambel is a brand of chili sauce products launched in 2018, and in 2020 the product strengthened its digital marketing strategy through the TikTok platform which significantly increased views. This research is to examine the role of storytelling ads that use funny characters and silly but relevant everyday stories. The method used is a qualitative research method including analysis of ad content and assisted by quantitative data in the form of a survey of TikTok application users. It aims to analyze how storytelling elements in Eatsambel ads on TikTok can influence audience engagement as measured by the number of views, likes, comments, and shares. In addition, this research seeks to identify visual elements and design principles that contribute to attracting attention and maintaining audience engagement with ad content. This is to emphasize the importance of brand association in the context of local product marketing, create a more personalized experience, and prove the effectiveness of making Eatsambel a brand that is discussed among the public.